Peran Penting Pengelolaan Manajemen Keuangan bagi Pelaku UMKM Diwilayah Kotabaru - Gusti Meinar Girda Ariani; Periyadi Periyadi; Ana Sofia Herawati; Edy Mahfuz; Hairul Hairul; Lamsah Lamsah (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2024)
One of the businesses that is affected by changes in times and technology is purun crafts . Based on observations, it shows that the biggest problem with the existence of this business is the inability to access the market in a sustainable manner. On the other hand, there is a limited amount of raw materials taken directly from nature in swamp areas that have been converted into housing, and a limited number of craftsmen. Other problems are related to the availability of skilled labor, product durability and the involvement of creativity in producing the product.